Alberta Oil Sands:: Fuel of the Future? - Carrigy, Maurice (Geoscience Canada, 1974)
Summary The Alberta Oil Sands, which contain more than 890 billion barrels of crude bitumen in place, will require the expenditure of vast sums of money to overcome the major environmental problems associated with the surface mining and hot-water washing method, and to develop a viable in-situ method of squeezing the oil from the subsurface deposits if they are to offset the predicted decline in Canada's conventional oil production.